2017
DOI: 10.1177/0954407016689515
|View full text |Cite
|
Sign up to set email alerts
|

Extremum-seeking algorithms for the emergency braking of heavy goods vehicles

Abstract: A pneumatic slip control braking system was demonstrated, which reduces the emergency stopping distances of heavy goods vehicles by up to 19%. Solutions are still required to set the optimal reference wheel slip for this system online, so that it can adapt to changing operating conditions. This paper considers whether the use of extremum-seeking algorithms is a feasible alternative approach to online tyre model fitting, the computational expense of which has, to date, inhibited real-time implementation. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Although this idealised performance could never be completely realised in the presence of disturbances, noise, uncertain parameters and bandwidth limits, it is a reasonable approximation of current high-bandwidth prototype systems. Accurate regulation of slip has been demonstrated in real vehicle tests with the CVDC's prototype system [11,22] and various methods have been proposed by which to estimate the optimum slip value for braking [10,23]. As SC technology continues to improve, the idealised SC model should become an ever more accurate approximation.…”
Section: Idealised Slip Controlmentioning
confidence: 99%
“…Although this idealised performance could never be completely realised in the presence of disturbances, noise, uncertain parameters and bandwidth limits, it is a reasonable approximation of current high-bandwidth prototype systems. Accurate regulation of slip has been demonstrated in real vehicle tests with the CVDC's prototype system [11,22] and various methods have been proposed by which to estimate the optimum slip value for braking [10,23]. As SC technology continues to improve, the idealised SC model should become an ever more accurate approximation.…”
Section: Idealised Slip Controlmentioning
confidence: 99%
“…9 WSR was carried out using grey system modelling by Kayacan et al, 17 using model predictive control (MPC), [18][19][20][21] using adaptive SMC, 7 and with an extremum seeking algorithm. 22 Force derivative based methods for WSR were proposed by Vignati and Sabbioni 11 and Capra et al, 14 which required wheel force sensing. First order actuator dynamics have been considered without any brake actuator controller.…”
Section: Introductionmentioning
confidence: 99%
“…11,15,16 Fast acting pneumatic valves were developed by Miller et al 23 for HCRVs, and utilised in the study by Henderson and Cebon, 8 and Morrison and Cebon. 22 In a few studies, 18,19,21 the brake actuator dynamics were incorporated in MPC formulation. A proportional-integral-derivative (PID) controller for brake actuator dynamics of an HCRV was proposed by Sridhar et al 24 Considering the attributes of various studies in literature, the following limitations were identified:…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al 12 also employed HiL simulation to simulate and evaluate an anti-lock brake system (ABS) algorithm developed for a bus. Miller et al 13 and Morrison and Cebon 14 also utilized HiL experiments to evaluate sliding mode control–based ABS algorithms for heavy road vehicles. Sridhar et al 15 developed a sliding mode control–based anti-lock braking algorithm for heavy vehicles and evaluated the same in a HiL setup consisting of brake hardware from a 4 × 2 HCRV, interfaced with IPG TruckMaker.…”
Section: Introductionmentioning
confidence: 99%